Współczesne problemy rozwoju administracji publicznej w Polsce - Kasiński, Michał (Annales. Etyka w Życiu Gospodarczym, 2011)
The article focusses on a critical analysis of basic problems that contemporary administration faces in the course of its transformation. The Author has stressed the role of the tendency of economize, citizen participation and deregulation of law. The Author has also shown how the reforms of the Polish administration reflect general globalization and europeization tendencies. He has also distinguished certain paculiarities of the Polish administrative transformation.